Quality of Life among Post PCI and CABG Patients with Coronary Heart Disease in Cardiac Outpatient Units Dr. Slamet Garut Hospital - Danis Aditia Syaputra; Aan Nur'aeni; Indra Maulana (Padjadjaran Acute Care Nursing Journal, 2021)
Implementing Percutaneous Coronary Intervention (PCI) and Coronary Artery    Bypass Graft (CABG) among CHD patients does not entirely eliminate the risk of recurrence, stenosis, and death. These conditions may affect the patient's physical, psychological, and social condition. Changes in these conditions influence the quality of life. Therefore, this study aimed to identify the quality of life of post PCI and CABG CHD patients.The study used a quantitative design with a cross-sectional approach. The sampling technique used convenience sampling and obtained 42 respondents for one month. The data collection was conducted at Dr. Slamet Garut's cardiac outpatient unit using the Indonesian version of the Quality of Life After Myocardial Infarction QLMI (MacNew) questionnaire. Data were analyzed using quantitative analysis.Based on the results of the data analysis, overall, respondents had a high quality of life. 71.4% of respondents had a high global quality of life. Whereas 73.8% had a high quality of life in the social domain, 71.4% had a high quality of life in the emotional domain, and 69.0% had a high quality of life in the physical domain.Most of the respondents had a high quality of life. However, there were identified that nearly one-third of patients had a low quality of life. The lowest score was presented in the physical domain. Thus, these findings indicate the need for support in the physical domain for the patient.